Hemithyroiditis - A Rare Scintigraphic Insight on Pertechnetate Thyroid Scan - Sana Munir Gill,; Laiba Talib Hussain,; Mairah Razi, (Journal of the Pakistan Medical Association, 2026)
Hemithyroiditis is a rare form of thyroid inflammation characterized by involvement of only one lobe of thyroid gland. The exact pathophysiological mechanism remains unclear; however, it is thought to represent a localized manifestation of chronic thyroiditis that may be triggered by upper respiratory tract infections, trauma and radiation exposure. It has a preponderance for middle aged women. Normally, most thyroiditis conditions (like Hashimoto’s or subacute thyroiditis) involve both lobes, but occasionally inflammation is confined to one side. We report a case of hemithyroiditis identified on a 99m-Tc pertechnetate thyroid scan, highlighting the importance of imaging in recognizing this uncommon presentation. Keywords: Doughnut box sign, Neuroendocrine tumours, Indium111 Octreotide scan.